Apoptosis in the nervous system - Nicotera, Pierluigi (Henry Stewart Talks, 2007)
Cell death programs in the nervous system, PCD, Similarities and differences in the classical PCD paradigm between worms and vertebrates, Conserved death mechanisms, Apoptosis, necrosis and autophagic cell death, Other death subroutines, The caspases, Intracellular ATP level, Common characteristics of cell death programmes in vertebrates, Different executioners and cell death routines, Brain ischemia, Calpain activation, Spatial control of cell death, Spatial control of neurodegeneration, BoNT/C, Mitochondrial dysfunction, Spatial control of cell death in central neurons